Oxidation of HMGB1 Is a Dynamically Regulated Process in Physiological and Pathological Conditions - Ferrara, Michele; Chialli, Ginevra; Ferreira, Lorena Maria; Ruggieri, Elena; Careccia, Giorgia; Preti, Alessandro; Piccirillo, Rosanna; Bianchi, Marco Emilio; Sitia, Giovanni; Venereau, Emilie (Frontiers in Immunology, 2020)
Acute inflammation is a complex biological response of tissues to harmful stimuli, such as pathogens or cell damage, and is essential for immune defence and proper healing. However, unresolved inflammation can lead to chronic disorders, including cancer and fibrosis. The High Mobility Group Box 1 (HMGB1) protein is a Damage-Associated Molecular Pattern (DAMP) molecule that orchestrates key events in inflammation by switching among mutually exclusive redox states. Fully reduced HMGB1 (fr-HMGB1) supports immune cell recruitment and tissue regeneration, while the isoform containing a disulphide bond (ds-HMGB1) promotes secretion of inflammatory mediators by immune cells. Although it has been suggested that the tissue itself determines the redox state of the extracellular space and of released HMGB1, the dynamics of HMGB1 oxidation in health and disease are unknown. In the present work, we analysed the expression of HMGB1 redox isoforms in different inflammatory conditions in skeletal muscle, from acute injury to muscle wasting, in tumor microenvironment, in spleen, and in liver after drug intoxication. Our results reveal that the redox modulation of HMGB1 is tissue-specific, with high expression of ds-HMGB1 in normal spleen and liver and very low in muscle, where it appears after acute damage. Similarly, ds-HMGB1 is highly expressed in the tumor microenvironment while it is absent in cachectic muscles from the same tumor-bearing mice. These findings emphasize the accurate and dynamic regulation of HMGB1 redox state, with the presence of ds-HMGB1 tightly associated with leukocyte infiltration. Accordingly, we identified circulating, infiltrating, and resident leukocytes as reservoirs and transporters of ds-HMGB1 in tissue and tumor microenvironment, demonstrating that the redox state of HMGB1 is controlled at both tissue and cell levels. Overall, our data point out that HMGB1 oxidation is a timely and spatially regulated process in physiological and pathological conditions. This precise modulation might play key roles to finetune inflammatory and regenerative processes.